On repentance and almsgiving - John Chrysostom, Saint, -407 (Fathers of the church, 1998)
St. John Chrysostom delivered nine homilies on repentance in Antioch of Syria sometime between 386 and 387. With conviction and certitude, he preached that repentance was a necessity for both the sinner and the righteous man. This volume presents Chrysostom's homilies on repentance and includes a sermon on almsgiving that he preached in Antioch during the winter months in 387.